A new circumscription of nissolia (Leguminosae-Papilionoideae-Dalbergieae), with Chaetocalyx as a New Generic Synonym - De Moura, Tânia M.; Gereau, Roy E.; Särkinen, Tiina E.; Fortuna-Perez, Ana P. [UNESP] (Missouri Botanical Garden Press, 2018)
Recent molecular phylogenetic studies have revealed Chaetocalyx DC. as a paraphyletic genus with Nissolia Jacq. nested within it, based on both nuclear ribosomal and plastid evidence. Considering the morphological similarity among the species of these two genera, which are vegetatively almost indistinguishable, we are here transferring the species of Chaetocalyx to Nissolia. Type information for all accepted species of Nissolia in its new circumscription is presented, including 16 new lectotype designations and the designation of one epitype. Diagnostic characters and information about the geographical distribution of each species are also noted. Nissolia s.l. is now represented by 30 taxa (29 species plus one variety) distributed from North to South America, with two centers of diversity found in Mexico and Brazil.
Keywords: Chaetocalyx; Fabaceae; Neotropics; new combination; Nissolia; systematics; taxonomy; typification